LINGUOCULTURAL FEATURES OF SPORTS TERMINOLOGY IN ENGLISH AND UZBEK (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the linguocultural features of sports terminology in English and Uzbek. By analyzing both traditional and modern sports terms, it highlights how language reflects cultural values, national identity, and intercultural communication. The study shows that English sports terminology tends to emphasize fairness, strategy, and globalization, whereas Uzbek terms emphasize honor, collective spirit, and historical continuity. A comparative analysis is provided to demonstrate the differences and similarities in cultural metaphors underlying sports terminology.